2020
DOI: 10.1186/s12906-020-02939-y
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatics investigation into the pharmacological mechanisms of javanica oil emulsion injection in non-small cell lung cancer based on network pharmacology methodologies

Abstract: Background: Javanica oil emulsion injection (JOEI) is an effective therapeutic option for patients with non-small cell lung cancer (NSCLC), but its mechanisms have not been fully elucidated. Methods: In this study, we utilized network pharmacology to systematically investigate the bioactive components and targets of JOEI, identify common targets in NSCLC, and understand and evaluate the underlying mechanism of JOEI in the treatment of NSCLC through expression level, correlation, enrichment, Cox, survival and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The effect of AGPS on the pathway network was analyzed in human glioma cells by sequencing and bioinformatics analysis, and it was discovered that AGPS silencing regulated tumor-related signaling pathways, such as the PI3K/Akt, Toll-like receptor, focal adhesion and VEGF signaling pathways. These aforementioned results were further validated by RT-qPCR, where significantly upregulated expression levels of THBS1 and ITGA11, and downregulated expression levels of SPP1, VEGFA, EGFR, IL7R, CXCL8, PTGS2 and SDC4, were all identified; all of these are crucial genes involved in the aforementioned signaling pathways, and have been found to serve roles in tumor metastasis and angiogenesis ( 18 23 ).…”
Section: Discussionmentioning
confidence: 75%
“…The effect of AGPS on the pathway network was analyzed in human glioma cells by sequencing and bioinformatics analysis, and it was discovered that AGPS silencing regulated tumor-related signaling pathways, such as the PI3K/Akt, Toll-like receptor, focal adhesion and VEGF signaling pathways. These aforementioned results were further validated by RT-qPCR, where significantly upregulated expression levels of THBS1 and ITGA11, and downregulated expression levels of SPP1, VEGFA, EGFR, IL7R, CXCL8, PTGS2 and SDC4, were all identified; all of these are crucial genes involved in the aforementioned signaling pathways, and have been found to serve roles in tumor metastasis and angiogenesis ( 18 23 ).…”
Section: Discussionmentioning
confidence: 75%
“…The two-dimensional structures of naringin were obtained from the PubChem Database, and AdipoR1 was obtained from the RCSB PDB database. Molecular docking was conducted by using AutoDock Vina software according to the published methods, and the results were analyzed by using PyMOL …”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking was conducted by using AutoDock Vina software according to the published methods, and the results were analyzed by using PyMOL. 21 Statistical Analysis. All experimental data were analyzed using GraphPad Prism 8 and SPSS 21 software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Clinical trials have demonstrated that Bruceae fructus can improve the effectiveness of treatment in patients with clinically advanced non-small cell lung cancer. [ 8 , 9 ] Bruceae fructus bitol is a key active component of the plant. [ 10 ] Bruceae fructus bitol has been shown in studies to suppress breast cancer, nasopharyngeal cancer, lung cancer, and other malignant tumors.…”
Section: Introductionmentioning
confidence: 99%